INTEGRAL KHUSUS - FATAHILLAH FATAHILLAH (Faktor Exacta, 2017)
In given the lecture for Mathematics or another names is Calculus we must following the based of Recana Perkuliahan Semester (RPS) and therefore we didn’t to introduction for student Specific Integrals and therefore we introduction specific integrals.